Predicting Gen Z’s Intention to Stay: The Role of Workplace Fun, Psychological Capital, and Work Engagement - Mufidawati, Handwita; Desiana, Putri Mega (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study aims to investigate the influence of workplace fun and psychological capital on Gen Z employees' intention to stay, and investigate the role of work engagement as a mediator in the relationship between the proposed variables. Design/Methods/Approach: Purposive sampling was used in this study. Data were obtained through an online survey distributed cross-sectionally, and 341 Gen Z employees working in Jabodetabek participated. The relationship between variables was analyzed through structural equation modeling (SEM) using Lisrel 8.51. Findings: The findings in this study show that workplace fun, psychological capital, and work engagement have a direct positive effect on intention to stay. Workplace fun and psychological capital also have a direct positive impact on work engagement. Furthermore, work engagement partially mediates the relationship between workplace fun and intention to stay, as well as psychological capital and intention to stay. Originality/Value: This research enriches the study of Gen Z in the workplace, focusing on the factors influencing Gen Z employees to stay. Furthermore, all industries and businesses from various sectors face the arrival of Gen Z, who will gradually become the primary workforce. The findings of this study extend the study of Gen Z employees within the scope of organizations from various sectors. Practical/Policy implication: Managers and organizations must foster a positive work environment with workplace fun to encourage Gen Z employees' willingness to stay. Furthermore, organizations must design appropriate ways to cultivate and preserve Gen Z employees' psychological capital and work engagement levels. This can be accomplished by offering innovative training and development, advancing career prospects, and involving Gen Z employees in achieving organizational objectives.